Comparative effects of two injection paths on performance of a heat pump with a sub-cooler injection configuration. (10th February 2020) - Tu, Qiu; Guo, Xiujuan; Zhang, Lina; Shao, Jingjing; Soldo, Vladimir; Boban, Luka; Ye, Fanging; Deng, Chenmian; Xu, Yonghua
Abstract: As one of the most promising and convenient heating service to replace coal-fired boilers and electric heaters due to its high energy efficiency, a heat pump has received more and more attention for the economical application and extensive research. The injection technology can be used to improve the heat pump performance. Currently, the injection ratio and pressure ratio are usually used to characterize the effects of injection styles on its performance. This is not conducive to its practical operation control because of additional cost increase. In this work, the effects of two injection cycles due to two injection paths were characterized with openings of a sub-cooling electronic expansion valve, comparatively tested and analyzed. Test results demonstrate that the heating capacities (Qh ), electricity power (EP) and coefficient of performance with the refrigerant injection into compressor (CRI) are more than those with the injection into accumulator (ARI), and the overall effect with the CRI is positive because the Qh improvement outperforms EP increase. For example, the maximum Qh with the CRI at 55, 60 and 85 rps were 8.1%, 7.7% and 18.3% higher than those without the CRI, and 7.3%, 6.7% and 19.0% higher than those with the ARI. The thermodynamic model was used to analyze the experimental results and expound the mechanism of the influence of injection path on the performance of heat pump. This work provides guidance for improving energy efficiency in common areas and enhancing Qh in cold areas.